Pengaruh Keaktifan Berorganisasi Terhadap Prestasi Akademik Mahasiswa Fisip Universitas Riau - Marpaung, Enggela .J.; Nurhamlin, Nurhamlin (Peneliti.net, 2025)
This research was conducted at FISIP Riau University, Pekanbaru, Riau. The purpose of this research is to find out: 1) The level of activeness of FISIP Riau University activists in the organization. 2) Academic achievement of activists who are active in organizing at FISIP Riau University. 3) The relationship between the activeness of activists in organizing with the academic achievement of activists FISIP Riau University. This research uses a quantitative approach with the type of inferential research. The population in this study were all students who participated in organizations or activists at FISIP Riau University, with a sample of 69 respondents taken by random sampling. Based on the results of the study, it can be concluded that there is an influence between organizational activeness on student academic achievement. This is evidenced by the F table value of 3.98 and F count of 63.135, where F count is greater than F table, which means that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Then, from the results of the T test that the effect of organizational activeness (X) in improving academic achievement (Y) with a significant value (sig) of 0.000 and a value of 0.05 so that the sig value is greater than the value of a equal to H0 is rejected which means there is an influence. Activist activism in organizations can be categorized as high, with an overall score of 3,636 which is in the interval 3222-4142. The academic achievement of activists is also categorized as high, with an overall score of 725 which is in the interval 646-830. The significance value (sig) of 0.000 is smaller than 0.05, which indicates a significant correlation between organizational activism (X) and academic achievement (Y). The calculated R value of 0.796 also indicates a high relationship or correlation between the two variables.